An educational intervention to update health workers about HIV and infant feeding. Issue 2 (17th December 2019) - Horwood, Christiane; Haskins, Lyn; Goga, Ameena; Doherty, Tanya; John, Vaughn; Engebretsen, Ingunn M.S.; Feucht, Ute; Rollins, Nigel; Kroon, Max; Sanders, David; Tylleskar, Thorkild
Abstract: Clinical guidelines are used to translate research findings into evidence‐based clinical practice but are frequently not comprehensively adopted by health workers (HWs). HIV and infant feeding guidelines were revised by the World Health Organization to align feeding advice for HIV‐exposed and unexposed infants, and these were adopted in South Africa in 2017. We describe an innovative, team‐based, mentoring programme developed to update HWs on these guidelines. The intervention was underpinned by strong theoretical frameworks and aimed to improve HWs' attitudes, knowledge, confidence, and skills about breastfeeding in the context of HIV. On‐site workshops and clinical mentoring used interactive participatory methods and a simple low‐tech approach, guided by participants' self‐reported knowledge gaps. Workshops were conducted at 24 participating clinics over three sessions, each lasting 1–2 hr. Evaluation data were collected using a self‐administered questionnaire. Of 303 participating HWs, 249/303 (82.2%) attended all workshops. Achieving high workshop attendance was challenging and "catch‐up" sessions were required to achieve good coverage. Common knowledge gaps identified included antiretroviral therapy adherence monitoring during breastfeeding and management of viral load results (173 participants), management of breast conditions (79), and advice about expressing and storing breastmilk (64). Most participants reported all their knowledge gaps were addressed and anticipated that their practice would change. We describe a feasible, sustainable approach to updating HWs on HIV and infant feeding guidelines and improving skills in breastfeeding counselling in resource‐constrained settings. This approach could be adapted to other topics and, with further evaluation, implemented at scale using existing resources.